WHAT THEY SAY ABOUT DEPRECIATION. - Hatfield, Henry R. (The Accounting Review, 1936)
Abstract One difficulty in discussing depreciation is in distinguishing between the fact of depreciation and the recording of the fact in the accounts. The fact is itself a physical or economic phenomenon. There is almost universal agreement that a physical asset does, in the process of use, wear out, at least to the extent of making its continued use uneconomical. The economic phenomenon which may be correlative with the physical phenomenon, but may often-times be independent thereof, is that with continued use of a physical asset the services which it renders tend to become exhausted. Hence, in the absence of disturbing outside influences, thee lessened number of service units which the asset remains capable of yielding are of less value than were the larger number originally embodied in the asset. Accounting does not concern itself with the actual wearing out of an object. But in so far as the wearing out of an asset, or the exhaustion of its potential services affects the value to be ascribed to the asset by the going concern, accounting is called upon to make some record of such changes.